2019
DOI: 10.1038/s41593-019-0415-2
|View full text |Cite
|
Sign up to set email alerts
|

A diversity of interneurons and Hebbian plasticity facilitate rapid compressible learning in the hippocampus

Abstract: The hippocampus is able to rapidly learn incoming information, even if that information is only observed once. Further, this information can be replayed in a compressed format in either forward or reverse modes during Sharp Wave Ripples (SPW-Rs). We leveraged state-of-the-art techniques in training recurrent spiking networks to demonstrate how primarily interneuron networks can: 1) generate internal theta sequences to bind externally elicited spikes in the presence of inhibition from Medial Septum, 2) compress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 77 publications
0
66
0
Order By: Relevance
“…Other studies have suggested that phase precession during spatial navigation could originate from a dual oscillator process (39, 50). Along this line, a recent model of the hippocampus uses the interference between two oscillators to model the neural dynamics related to spatial navigation (51). Although this model shares similarities with ours, a fundamental difference is that our model uses the phase of combined oscillators to create a unique input at every time-step of a task, whereas their model relies on the beat of the combined frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that phase precession during spatial navigation could originate from a dual oscillator process (39, 50). Along this line, a recent model of the hippocampus uses the interference between two oscillators to model the neural dynamics related to spatial navigation (51). Although this model shares similarities with ours, a fundamental difference is that our model uses the phase of combined oscillators to create a unique input at every time-step of a task, whereas their model relies on the beat of the combined frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…during the 100 ms step and by ν Xµ (t) = ν Xbg (11) during only background activity. Parameter α Xν is a scalar that sets the ratio of excitatory and inhibitory firing rate.…”
Section: Methods Of Complementary Inhibitory Weight Profiles Emerge Fmentioning
confidence: 99%
“…I nhibitory neurons exhibit large variability in morphology, connectivity motifs, and electrophysiological properties [1][2][3][4] . Inhibition often balances excitatory inputs, thus stabilising neuronal network activity 5,6 and allowing for a range of different functions [7][8][9][10][11] . When both inhibitory and excitatory inputs share the same statistics and their weight profiles are similar 12 , the resulting state of the postsynaptic neuron is one of precise balance of input currents 9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Touretzky and Redish 1996;Samsonovich and McNaughton 1997;Cutsuridis and Hasselmo 2012;Saravanan et al 2015;Erdem et al 2015;Stachenfeld et al 2017), however, there is still ongoing debate particularly on the mechanisms (e.g. Foster 2017; Liu et al 2018b;Matheus Gauy et al 2018;Nicola and Clopath 2019) and the functional role of temporal activity patterns (Liu et al 2018a). In contrast to technical systems, where autonomous localization methods are based on a costly collection of extensive series of sensory snapshots (Davison et al 2007;Milford and Wyeth 2012;Siam and Zhang 2017), the prevalent idea in neuroscience is that, in mammals, the hippocampal space code arises from efficient internal dynamics that is locked to places of salient sensory features (Keinath et al 2018) thereby saving the synaptic resources for explicitly memorizing all details of place-specific sensory inputs.…”
Section: Introductionmentioning
confidence: 99%